Peran Dewan Pengawas Syariah dalam Penetapan Biaya Tagih dan Denda Murabahah di BMT Bina Insan Mandiri Karanganyar - Putra, Ressa Ananda; Rosidah, Zaidah Nur (Jurnal Hukum Ekonomi Syariah, 2025)
The rapid growth of Sharia-based financial institutions in Indonesia shows a significant trend, where BMT or Sharia cooperatives have become one of the most favored Sharia financial institutions by the community. In Murabahah financing at KSPPS BMT Bina Insan Mandiri Karanganyar, there is an application of collection fees for visits to the homes of customers who experience delayed payments, as well as penalties for late installments. According to Sharia principles, the practice of charging penalties for late installment payments is not permitted. This raises questions about the compliance of financing practices with Sharia principles and the implementation guidelines of Murabahah based on the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Number 04/DSN-MUI/IV/2000, which requires the contract to be free from usury (riba). This study aims to analyze the determination of collection fees and penalty charges for late installment payments by customers, as well as to examine the role of the Sharia Supervisory Board in overseeing these two aspects in Murabahah financing. The method used in this study is field research with a qualitative approach. The results show that collection fees are a form of operational costs, such as fuel expenses, incurred to conduct visits to customers’ homes. Meanwhile, penalty charges are imposed due to customers' late installment payments. According to the Sharia Supervisory Board, collection fees can be categorized as ta’widh (compensation), while penalty charges fall under ta’zir (sanction). Keyword: Sharia Supervisory Board, Ta’widh, Ta’zir